Respuesta :
The x in this equation is the first number in the brackets, and the result of the equation is the second number in the brackets. So all that needs to be done is to substitute x for 3, 2 and 4 and see which one has the correct answer.
3 X 2 = 6. 6 - 5 = 1 (3, 1)
2 X 2 = 4. 4 - 5 = -1 (2, -1)
4 X 2 = 8. 8 - 5 = 3 (4, 3)
The only one of those coordinates that are the same as any of the given answers are (2, -1). Therefore, that is the answer.
3 X 2 = 6. 6 - 5 = 1 (3, 1)
2 X 2 = 4. 4 - 5 = -1 (2, -1)
4 X 2 = 8. 8 - 5 = 3 (4, 3)
The only one of those coordinates that are the same as any of the given answers are (2, -1). Therefore, that is the answer.